PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2013 - 2017 - Kusrawan dan Fitriana (Jurnal Manajemen Lakidende: Economic & Business, 2019)
This study aims to determine the magnitude of the influence of Capital Structure and Firm Size on Profitability in Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. The population in this study amounted to 144 Manufacturing Companies listed on the Indonesia Stock Exchange (IDX), with sampling techniques using purposive sampling techniques with certain criteria, so that the sample of this study amounted to 19 companies. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that simultaneously Capital Structure and Company Size variables affect the Profitability of Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. Partially the Capital Structure proxied by DER (Debt Equity Ratio) has an effect on profitability, while the Capital Structure proxied by TIE (Time Interest Earned) has no effect on Profitability, and the Company Size variable has no effect on Profitability